Learning to Become Youth. An Action Theory Approach - Mørch, Sven (Outlines. Critical Practice Studies, 2006)
Youth is a historical construction and an answer to a specific challenge of individualisation in biography. And, as a historical and social construction, youth has to be learned. This article focuses on youth development from an action or activity theory perspective and as a learning process. It demonstrates how different youth problems and forms of youth differentiation follow forms of youth learning. Moreover, it shows how late modern development creates the demand for a new non-formal learning perspective to secure the development of new forms of competence. Based on Danish research concerning peer learning as a non-formal learning context, some perspectives of peer-learning competence are discussed.